Enhancing Fine Motor Skills Through Collage Activities Using Natural Materials in Kindergarten - Ernawati Ernawati; Nur Rahmah; Pertiwi Kamariah Hasis (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Fine motor skills are essential for childrenÔÇÖs developmental readiness, supporting their ability to perform daily tasks and foundational academic activities. This study aims to improve fine motor skills in early childhood through collage activities using diverse natural materials. Adopting a classroom action research design with the John Elliot model, the research was conducted in two cycles, each comprising three meetings. Eleven children aged 5ÔÇô6 years participated, with data collected via interviews, observations, and documentation, analyzed both descriptively and quantitatively. The findings showed a gradual increase in fine motor skill achievement: 38% of indicators were unmet in the pre-action phase, rising to 62% in the first cycle, and reaching 92% in the second cycle, indicating significant improvement. Activities such as squeezing, tearing, cutting, and pasting natural materials fostered sensory and motor engagement. In conclusion, collage activities with natural materials are effective in enhancing fine motor skills. It is recommended that educators integrate such creative, nature-based approaches to support childrenÔÇÖs motor development.┬á┬á